2009
DOI: 10.1002/met.143
|View full text |Cite
|
Sign up to set email alerts
|

Regional scale spatio‐temporal consistency of precipitation variables related to water resource management and planning

Abstract: ABSTRACT:The focus of this research was to determine the extent of spatio-temporal changes in precipitation patterns using methods that can be regionalized and applied to various water resources such as lakes, streams, reservoirs or other water bodies. Many water resources throughout the world have demonstrated changes in historic water levels. As precipitation is the major input to these water bodies, it is important to investigate any changes in rainfall in both time and space. To investigate these patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Paynter and Nachabe (2009) found that west-central Florida rainfall patterns are spatially homogenous and temporally stationary and no significant shifts that would correlate to trends in lake levels were evidenced. For the present study, the authors selected two lakes undergoing rapid urbanization within the west-central Florida region based on the availability of sufficient data, lack of direct lake withdrawals and lack of proximity to wellfields.…”
Section: Lake Information and Datamentioning
confidence: 90%
See 1 more Smart Citation
“…Paynter and Nachabe (2009) found that west-central Florida rainfall patterns are spatially homogenous and temporally stationary and no significant shifts that would correlate to trends in lake levels were evidenced. For the present study, the authors selected two lakes undergoing rapid urbanization within the west-central Florida region based on the availability of sufficient data, lack of direct lake withdrawals and lack of proximity to wellfields.…”
Section: Lake Information and Datamentioning
confidence: 90%
“…• Rainfall records were nearly 100% complete for the time periods analyzed, however, none of the lakes had gages located immediately at the lakes themselves but were within 2 to 6 km of the lakes analyzed. This is well within an acceptable range for this analysis (Paynter and Nachabe 2009) but there will be slight variability between gage site and lake rainfall amounts. • Although evaporation is highly correlated with temperature, it is also dependent on wind, humidity and other factors for which data were not available.…”
Section: Lag (Weeks)mentioning
confidence: 92%